2023
DOI: 10.9734/ijpss/2023/v35i22753
|View full text |Cite
|
Sign up to set email alerts
|

Personal, Socio-economic and Psychological Characteristics of Horticulture Crop Growers Practicing Protected Cultivation: A Critical Analysis

Abstract: The study was conducted during 2020 in Chikkaballapur district which comes under eastern dry zone (Zone-V) of Karnataka. In Chikkaballapur district, two taluks i.e. Sidlaghatta and Chikkaballapur taluks were purposefully selected for the stud, since this taluk are having more area under protected cultivation technology. The ex-post-facto research design was used for the study In the present investigation, ex-post facto research design was used. This design was considered appropriate, as it is a systematic empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Farmers' medium accomplishment drive may be attributed to a number of factors, including their limited land holdings, primary school education, and social and economic circumstances, which may have prevented them from having a higher achievement orientation. The results are conformity with study conducted by Rajesh (2020) [5] .…”
Section: Achievement Motivationsupporting
confidence: 92%
“…Farmers' medium accomplishment drive may be attributed to a number of factors, including their limited land holdings, primary school education, and social and economic circumstances, which may have prevented them from having a higher achievement orientation. The results are conformity with study conducted by Rajesh (2020) [5] .…”
Section: Achievement Motivationsupporting
confidence: 92%
“…The major constraint perceived by the capsicum growers (Table 2) was fluctuations in market prices and demand, leading to the poor income to farmers followed by lack of specialised supply chain management practices. Rajesh & Shivalingaiah (2022) and Saravanan (2012) opined that problem of lack of suitable cold storage facilities (57.63%) and Singla et al (2021) observed lack of market information (57.42%) as major marketing constraints. Saini (2012) emphasized the importance of Government intervention in the price policy mechanism to prevent price fluctuation.…”
Section: Market Constraintsmentioning
confidence: 99%